Skills and work organisation in Britain: a quarter century of change - Francis Green; Alan Felstead; Duncan Gallie; Golo Henseke (Journal for Labour Market Research, 2016)
This paper overviews key findings concerning the evolution of job skill requirements in Britain, and their relationship to technology and work organisation, based on surveys dating from 1986. The use of skills has been rising, as indicated by several indicators covering multiple domains. Technological change is robustly implicated in these rises, but it is not possible to satisfactorily classify most tasks according to how easily they are encoded and thereby clearly link the changes to the nuanced theory of skill-biased technical change associated with asymmetric employment polarisation. Moreover, changing work organisation also contributes to explaining the rises, both in skills use and in skills development. Nevertheless, the extent of worker autonomy in the workplace declined notably during the 1990s; this decline is not accounted for by the data, but is thought to be associated with changing management culture. Changing skill requirements also affect pay. In addition to the education level both computing skills and influence skills attract a premium in the labour market. There is an increasing cost in terms of pay from overeducation and a rising prevalence of overeducation. Together, these changes are reflected in an increased dispersion of the graduate pay premium. While these findings have provided important contextual information for the development of skills policies, they have had little effect on engendering policies for stimulating improved job design.
Keywords: J2; J3; 330; Qualifikationsanforderungen - Entwicklung; Arbeitsorganisation; organisatorischer Wandel - Auswirkungen; technischer Wandel - Auswirkungen; Qualifikationsverwertung; berufliche Autonomie; Führungsstil; Unternehmenskultur; Lohnentwicklung; Überqualifikation; Einkommenseffekte; Bildungsertrag; EDV-Kenntnisse; Akademiker; Großbritannien